2014
DOI: 10.1007/s00405-014-3394-7
|View full text |Cite
|
Sign up to set email alerts
|

The development and treatment of periprosthetic leakage after prosthetic voice restoration. A literature review and personal experience part I: the development of periprosthetic leakage

Abstract: In the past 30 years, the use of a voice prosthesis has become the treatment of choice for the restoration of speech following laryngectomy. Not only is the placement of a voice prosthesis a simple surgical procedure, but it is also associated with a low rate of complications and an excellent success rate. Approximately, 20-30 % of all patients with voice prostheses, however, develop periprosthetic leakage with aspiration over time. Periprosthetic leakage is usually caused by an enlargement of the tracheo-oeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 136 publications
7
48
0
1
Order By: Relevance
“…Following total laryngectomy for laryngeal cancer, vocal rehabilitation often involves the creation of a tracheoesophageal fistula (TEF) and insertion of a voice prosthesis . The placement of a voice prosthesis immediately postlaryngectomy is advantageous because it provides both primary voice restoration and allows for immediate voice rehabilitation . A literature review by Lorenz revealed success rates of 85% to 95% for voice restoration with modern prostheses following laryngectomy .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Following total laryngectomy for laryngeal cancer, vocal rehabilitation often involves the creation of a tracheoesophageal fistula (TEF) and insertion of a voice prosthesis . The placement of a voice prosthesis immediately postlaryngectomy is advantageous because it provides both primary voice restoration and allows for immediate voice rehabilitation . A literature review by Lorenz revealed success rates of 85% to 95% for voice restoration with modern prostheses following laryngectomy .…”
Section: Introductionmentioning
confidence: 99%
“…Further, these patients often require radiation therapy, which can lead to pharyngoesophageal stenosis (PES) . Krause et al and Pattani et al postulated that the development of strictures in the pharyngoesophageal region may predispose to periprosthetic leakage . Narrowing of this region increases flow rate and pressure during bolus transport through this segment of the upper aerodigestive tract, resulting in leakage and a widening of the fistula tract surrounding the voice prosthesis .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations